Responsibility Centres and Internal Assignment Prices - Corina-Graziella BÂTCĂ-DUMITRU; Daniela-Nicoleta SAHLIAN; Cleopatra ȘENDROIU (CECCAR Business Review, 2022)

(untitled)
In the article hereby we present aspects regarding the responsibility centres and what they represent, respectively, the types of responsibility centres and the decisions about choosing the type of such a centre, as well as regarding the internal assignment prices and the methods for their setting.